Bifidobacterium animalis ssp. lactis CNCM-I2494 Restores Gut Barrier Permeability in Chronically Low-Grade Inflamed Mice - Martín, Rebeca; Laval, Laure; Chain, Florian; Miquel, Sylvie; Natividad, Jane; Cherbuy, Claire; Sokol, Harry; Verdu, Elena F.; van Hylckama Vlieg, Johan; Bermudez-Humaran, Luis G.; Smokvina, Tamara; Langella, Philippe (Frontiers in Microbiology, 2016)
Growing evidence supports the efficacy of many probiotic strains in the management of gastrointestinal disorders associated with deregulated intestinal barrier function and/or structure. In particular, bifidobacteria have been studied for their efficacy to both prevent and treat a broad spectrum of animal and/or human gut disorders. The aim of the current work was thus to evaluate effects on intestinal barrier function of Bifidobacterium animalis subsp lactis CNCM-I2494, a strain used in fermented dairy products. A chronic DNBS-induced low-grade inflammation model causing gut dysfunction in mice was used in order to study markers of inflammation, intestinal permeability and immune function in the presence of the bacterial strain. In this chronic low-grade inflammation mice model several parameters pointed out the absence of an over active inflammation process. However, gut permeability, lymphocyte populations and colonic cytokines were found to be altered. B. animalis subsp lactis CNCM-I2494 was able to protect barrier functions by restoring intestinal permeability, colonic goblet cell populations and cytokine levels. Furthermore, tight junction (TJ) proteins levels were also measured by qRT-PCR showing the ability of this strain to specifically normalize the level of several TJ proteins, in particular for claudin-4. Finally, B. lactis strain counterbalanced CD4+ lymphocyte alterations in both spleen and mesenteric lymphoid nodes (MLN). It restores the Th1/Th2 ratio altered by the DNBS challenge (which locally augments CD4+ Th1 cells) by increasing the Th2 response as measured by the increase in the production of major representative Th2 cytokines (IL-4, IL-5 and IL-10). Altogether, these data suggest that B. animalis subsp lactis CNCM-I2494 may efficiently prevent disorders associated with increased barrier permeability.